Innovation in natural resource management: the role of property rights and collective action in developing countries - Meinzen-Dick, Ruth S.; Knox, Anna; Place, Frank; Swallow, Brent M. (International Food Policy Research Institute, 2002)
International agricultural research is expanding beyond the development of annual crop technologies for individual farms to the development of longer-tern natural resource management techniques for entire landscapes. But technologies of practices with a long lag time between investment and returns are unlikely to be adopted by farmers unless they have secure rights to the underlying resources (property rights). Similarly, technologies that span multiple farms are unlikely to be adopted unless neighbors and groups work together (collective action). But little is know about the way property rights and collective action in developing countries mediate the adoption of technologies by farmers and groups. To address this information gap, this volume brings together international experts in economics, sociology, and natural resource management to examine the links among property rights, collective action, and technological change for a variety of technologies across a rage of community contexts in the developing world. -- from Authors' abstract."